sgRNA Knock-in Mouse Provides an Alternative Approach for In Vivo Genetic Modification - Zhang, Lichen; Li, Wushan; Liu, Zhuangzhuang; Liu, Yang; Liu, Zhilong; Gu, Yanrong; He, Le; Zhou, Binhui; Li, Tianhan; Chao, Tianzhu; Liang, Yinming; Lu, Liaoxun (Frontiers in Cell and Developmental Biology, 2022)
Functional genomics in mammalian model such as in mice are fundamental for understanding human biology. CRISPR/Cas9 system dramatically changed the tempo of obtaining genetic mouse models due to high efficiency. However, experimental evidence for establishment of sgRNA knock-in animals and analyses of their value in functional genomics are still not sufficient, particularly in mammalian models. In this study, we demonstrate that establishment of sgRNA knock-in mice is feasible, and more importantly crosses between sgRNA knock-in mice and the Cas9 constitutively expressing mice result in complete deletion of the target gene. Such sgRNA knock-in provides alternative approach for in vivo genetic modification and can be useful in multiple circumstances such as maintenance of genetically modified animals which are difficult to breed as homozygotes, and cross of such mice to diverse genomic backgrounds to obtain genetically modified animals.